Comparison of two pre-enrichments broths for recovering Listeria spp. from salmon (Salmo salar) and salmon-trout (Oncorhynchus mykiss) - Vaz-Velho, Manuela (2001)
Low levels of occurrence of Listeria spp. in fresh salmon (Salmo_salar ) and salmon-trout (Oncorhynchus mykiss), may be related to the selectivity of the pre-enrichment broth recommended by ISO 11290-1. The purpose of this study was to compare the abilities of Fraser base (without supplements) and 0.1% (w/v) peptone water for recovering Listeria spp. from the fresh fish samples. Fifty-six fish were swabbed and the swabs placed in Fraser base and in 0.1% (w/v) peptone water. Samples were analysed 4–6 h later following the ISO 11290-1 protocol. A total of fifteen Listeria spp. positive samples were found. Three and twelve samples were found to contain respectively, L. monocytogenes and L. innocua. The Fraser base did not detect any of the three L. monocytogenes positive samples. Only two Listeria spp. positive samples were simultaneously recovered by the two broths.